Added Prognostic Value of Hemorrhagic Transformation Quantification in Patients With Acute Ischemic Stroke - van Kranendonk, Katinka R.; Treurniet, Kilian M.; Boers, Anna M. M.; Berkhemer, Olvert A.; Coutinho, Jonathan M.; Lingsma, Hester F.; van Zwam, Wim H.; van der Lugt, Aad; van Oostenbrugge, Robert J.; Dippel, Diederik W. J.; Roos, Yvo B. W. E. M.; Marquering, Henk A.; et al. (Frontiers in Neurology, 2020)
Introduction and aim Hemorrhagic transformation (HT) occurs frequently after acute ischemic stroke and negatively influences functional outcome. Usually, HT is classified by its radiological appearance. Discriminating between the subtypes can be complicated and inter-observer variation is considerable. Therefore, we aim to quantify rather than classify hemorrhage volumes and determine the association of hemorrhage volume with functional outcome in comparison to the ECASS II classification. Patients and methods We included patients from the MR CLEAN trial with follow-up imaging. Hemorrhage volume was estimated by manual delineation of the lesion and HT was classified according to the ECASS II classification (petechial hemorrhagic infarction type 1 (HI1) and 2 (HI2), parenchymal hematoma type 1 (PH1) and 2 (PH2)) on follow-up CT 24 hours to 2 weeks after treatment. We assessed functional outcome using the modified Rankin Scale (mRS) 90 days after stroke onset. Ordinal logistic regression with and without adjustment for potential confounders was used to describe the association of hemorrhage volume with functional outcome. We created regression models including and excluding total lesion volume as a confounder. Results We included 478 patients. Of these patients, 222 had HT. Median hemorrhage volume was 3.37 ml [0.80-12.6] and per HT subgroup; HI1: 0.2[0.0-1.7], HI2: 3.2[1.7-6.1], PH1: 6.3[4.2-13] and PH2: 47[19-101]. Hemorrhage volume was associated with functional outcome (acOR 0.83,95CI:0.73-0.95) but not anymore after adjustment for total lesion volume (acOR:0.99,95%CI:0.86-1.15, per 10 ml). Hemorrhage volume in patients with PH2 was significantly associated with functional outcome after adjustment for total lesion volume (acOR:0.70,95%CI:0.50-0.98). Conclusion Hemorrhagic transformation volume is associated with functional outcome in patients with acute ischemic stroke but not indepdent of total lesion volume. The extent of a PH2 was associated with outcome, suggesting that measuring hemorrhage volume only provides additional benefit in prediction of outcome when a PH2 is present.